Respuesta :
Answer:
x1 = 2.79129, x2 = 1.79129
Step-by-step explanation:
x^2-5-x
x^2-5+x=0
x^2+x-5=0
-1+-square root od=f 1^2 - 4x1x(-5) / 2x1 = -1+- square root of 21 (add numbers together) / 2
then solve the formula with a plus sign instead of +- then and solve the formula with a - this time and you should get x1 = 2.79129, x2 = 1.79129, or -1 +square root of 21 (add numbers together) / 2 and -1 - square root of 21 (add numbers together) / 2
For this case we must solve the following equation:
[tex]x ^ 2 = 5-x[/tex]
By manipulating algebraically we have:
[tex]x ^ 2 + x-5 = 0[/tex]
The quadratic formula is given by:
[tex]x = \frac {-b \pm \sqrt {b ^ 2-4 (a) (c)}} {2a}[/tex]
We have to:
[tex]a = 1\\b = 1\\c = -5[/tex]
Substituting we have:
[tex]x = \frac {-1 \pm \sqrt {1 ^ 2-4 (1) (- 5)}} {2 (1)}\\x = \frac {-1 \pm \sqrt {1 + 20}} {2}\\x = \frac {-1 \pm \sqrt {21}} {2}[/tex]
So, we have two roots:
[tex]x_ {1} = \frac {-1+ \sqrt {21}} {2} = 1,7913\\x_ {2} = \frac {-1- \sqrt {21}} {2} = - 2.7913[/tex]
Answer:
[tex]x_ {1} = \frac {-1+ \sqrt {21}} {2}\\x_ {2} = \frac {-1- \sqrt {21}} {2}[/tex]